Differences in Maternal Temperature During Labour With Remifentanil Patient-controlled Analgesia or Epidural Analgesia: A Randomised Controlled Trial. Issue 3 (September 2016) - Douma, M.R.; Stienstra, R.; Middeldorp, J.M.; Arbous, M.S.; Dahan, A.
Abstract : ( Int J Obstet Anesth. 2015;24(4):313–322) Two popular techniques for the treatment of labor pain are epidural analgesia (EA) and intravenous remifentanil patient-controlled analgesia (RPCA). Remifentanil is a μ-opioid receptor agonist with a rapid onset of action and short latency to peak analgesic effect. This randomized, controlled trial was performed to compare the rate of maternal fever (temperature ≥38°C) in parturients receiving RPCA with those receiving either EA or no analgesia. The authors hypothesized that fever would be more prevalent in patients receiving EA compared with patients receiving either RPCA or no analgesia. The secondary objectives studied included differences in maternal oxygen saturation (SpO2 ), nausea, vomiting, sedation, pruritus, hypotension, and neonatal outcome.